Speaking in God's name : Islamic law, authority, and women - Abou El Fadl, Khaled, 1963-; Alexander Street Press (Oxford : Oneworld, 2006)
Drawing on both religious and secular sources, this challenging book argues that divinely ordained law is frequently misinterpreted by Muslim authorities at the expense of certain groups, including women. Khaled Abou El Fadl cites a series of injustices in Islamic society and ultimately proposes a return to the original ethics at the heart of the Muslim legal system.
Online access provided by Alexander Street Press as part of: Twentieth century religious thought. Volume II, Islam.
Includes bibliographical references (pages 310-340), glossary, and index.
Keywords: Women (Islamic law); Women in Islam; Muslim women